Perancangan Sistem Evaluasi Online Dengan Fitur Link Login Instant Menggunakan Model Waterfall - Imam Sutoyo (Paradigma, 2021)
The Covid-19 pandemic that has hit the world has an impact on the implementation of an online learning system for all levels of education. For the purposes of student evaluation, of course, an online evaluation system is needed. At the basic education level, the online evaluation system must be specially designed by prioritizing the ease of students accessing and carrying out evaluations. Therefore, research is needed to design an online evaluation system that is easy to use and flexible. This study aims to design an online evaluation system that can be accessed by students by simply clicking a link. So students do not need to create an account and use it to access teacher evaluations. The expected result of this research is a system that makes it very easy, especially for students at the basic education level so that all students can follow all evaluations given by the teachers easily and flexibly. Unified Modeling Language is used to make the design, while the method for system development used is the waterfall model.